Discourse of ‘Dysfunction’: Sentencing Narratives and the Construction of Indigenous Offending - Bond, Christine (2011)
Using a narrative analysis of judges sentencing remarks in South Australian higher courts, we explore whether broader discourses ‘dysfunction’ ‘disorganisation’, ‘deprivation’ and ‘pathology’ impact understandings of Indigenous offending and subsequent constructions of Indigenous defendants in the sentencing process.Sydney Institute of Criminology; School of Social Sciences at the University of Western Sydne